2017
DOI: 10.3390/catal7120354
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Oxidation of Salicyl Alcohols Catalyzed by Lipase

Abstract: Abstract:A novel and efficient oxidation of salicyl alcohols to the corresponding salicylaldehydes catalyzed by lipase is reported for the first time. Under the optimal reaction conditions, the method exhibited high yields (81-95%) and selectivities for salicylaldehydes. Moreover, this study expands the application of enzyme catalytic promiscuity in organic synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Moreover, hot deformation behavior of as-cast 30Cr2Ni4MoV steel using processing maps was discussed by Zhou [12]. Grain boundary segregation and precipitation during the plastic deformation of 30Cr2Ni4MoV steel were studied [13].…”
Section: Intrduction mentioning
confidence: 99%
“…Moreover, hot deformation behavior of as-cast 30Cr2Ni4MoV steel using processing maps was discussed by Zhou [12]. Grain boundary segregation and precipitation during the plastic deformation of 30Cr2Ni4MoV steel were studied [13].…”
Section: Intrduction mentioning
confidence: 99%
“…Recently, a novel asymmetric synthesis method to prepare an enantiomerically enriched precursor of lamivudine through whole cell catalysis mediated by Klebsiella oxytoca was reported . Among numerous biocatalysts, a family of lipases are widely used in the synthesis of chiral molecules, which are known to have catalytic promiscuity showing good catalytic abilities in C–C, C–N, C–O, and C–S bond formations. Subtilisin was also applied to the asymmetric synthesis of lamivudine. Hu et al presented a cascade addition–cyclization–acetylation reaction to prepare the enantioenriched 1,3-oxathiolane structure via a novel surfactant-treated subtilisin Carlsberg (STS)-catalyzed dynamic kinetic resolution protocol in which the racemic substrate was continuously converted to the desired target enantiomer by efficiently coupling with enzyme catalysis. , Dynamic kinetic resolution protocols were used in many complex resolution systems. , The stereoconfiguration of the 1,3-oxathiolane intermediate could be effectively controlled by different types of enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few years, many reports have demonstrated that lipase could catalyze the in situ generation of peracids through a perhydrolysis of carboxylic acids or esters (6,7). And the in situ formed peracids have been successfully utilized in many oxidations, such as epoxidation of alkenes, Baeyer-Villiger reaction, Dakin oxidation, oxidations of amines, alcohols and sulfanyl compounds (8)(9)(10)(11)(12)(13)(14)(15). These oxidative processes are representative examples of enzyme catalytic promiscuity, which is a term used to describe an enzyme that can catalyze chemical reactions fully different than physiological ones (16).…”
Section: Introductionmentioning
confidence: 99%